The Effect of the Cooperative Learning Model of Team Games Tournament Type on Students' Learning Outcomes in the Subject of the Qur'an Hadith At MTs Al-Ahsan Bogor - Siti Nur Rizky Muthmainnah; Nurhasan (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2026)
This study discusses the effect of team games tournament-type cooperative learning model on student learning outcomes in the Qur'an Hadith class VIII at MTs Al-Ahsan Bogor. This study aims to determine the learning outcomes of the Qur'an Hadith in the control group at this school, to determine the learning outcomes of the Qur'an Hadith in the experimental group at this school, and to determine the effect of team games tournament-type cooperative learning model on student learning outcomes in the Qur'an Hadith at this school. The researchers used a quantitative approach and quasi-experimental method, with data collected through learning outcomes tests given to 40 students in the control group and 40 students in the experimental group. The study results showed that (1) the average score of post-test learning outcomes for the experimental group was 85.15, (2) the average score of post-test learning outcomes for the control group was 67.38, (3) the results of the independent sample t-test test resulted in a t value of 7.834 with a value of Sig. (2-tailed) 0.00 <0.05 indicates a significant effect of the team games tournament type cooperative learning model on student learning outcomes in the Qur’an Hadith subjects in class VIII at MTs Al-Ahsan Bogor City. Therefore, this study accepts the alternative hypothesis (Ha) and rejects the null hypothesis (Ho). Therefore, if schools want to improve student learning outcomes, they should choose appropriate and effective learning models to create a conducive and enjoyable learning environment. This study contributes to the existing body of knowledge by providing new insights into the research topic, addressing gaps identified in previous studies, and offering practical recommendations for researchers, practitioners, and policymakers. Furthermore, the findings can serve as a reference for future studies and support the development of more effective strategies in the field.